2019
DOI: 10.1002/dmrr.3176
|View full text |Cite
|
Sign up to set email alerts
|

Impaired awareness of hypoglycaemia: A new risk factor for adverse pregnancy outcomes in type 1 diabetes

Abstract: Aim The aim of this study is to evaluate the impact of impaired awareness of hypoglycaemia (IAH) on metabolic control and pregnancy outcomes in women with type 1 diabetes. Material and Methods This was a single‐centre prospective cohort study of singleton pregnant women with type 1 diabetes. IAH was assessed at the first antenatal visit using Clarke's test (score ≥ 3). Data on metabolic control, hypoglycaemic events, and the lipid profile were collected from prior to pregnancy and in each trimester of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 41 publications
1
19
2
1
Order By: Relevance
“…After adjusting for risk factors such as gestational hypertension, triglyceride, fetal distress in utero and premature delivery, multivariate logistic regression revealed that maternal FBG level in the second trimester of pregnancy was associated with a decreased risk of NA [(AOR 0.26; 95% CI 0.08 to 0.80) per mmol/L increase in FBG level in the second trimester of pregnancy], which was unreported in previous studies. The results from a study evaluating hypoglycemia and adverse pregnancy outcomes in women with type 1 diabetes, impaired awareness of hypoglycemia (IAH) was associated with an increased risk of neonatal respiratory distress (AOR 11.24, 95% CI 1.01-124.9) [27], were similar to our ndings. Additionally, maternal FPG in the third trimester was not signi cantly associated with asphyxia in our study.…”
Section: Discussionsupporting
confidence: 85%
“…After adjusting for risk factors such as gestational hypertension, triglyceride, fetal distress in utero and premature delivery, multivariate logistic regression revealed that maternal FBG level in the second trimester of pregnancy was associated with a decreased risk of NA [(AOR 0.26; 95% CI 0.08 to 0.80) per mmol/L increase in FBG level in the second trimester of pregnancy], which was unreported in previous studies. The results from a study evaluating hypoglycemia and adverse pregnancy outcomes in women with type 1 diabetes, impaired awareness of hypoglycemia (IAH) was associated with an increased risk of neonatal respiratory distress (AOR 11.24, 95% CI 1.01-124.9) [27], were similar to our ndings. Additionally, maternal FPG in the third trimester was not signi cantly associated with asphyxia in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, this atherogenic pattern seems to persist 6 years after any kind of gestational hypertensive disorder, including pre‐eclampsia 19 . Among the pregnant T1D population, however, the relationship with lipid parameters has been scarcely studied, with contradictory findings so far 17,31 . Our results suggest that, even almost 10 years after this obstetric disorder, pre‐eclampsia could be associated with some subtle changes in triglyceride‐related variables.…”
Section: Discussionmentioning
confidence: 60%
“…Our results suggest that, even almost 10 years after this obstetric disorder, pre‐eclampsia could be associated with some subtle changes in triglyceride‐related variables. These changes, which are completely overlooked in the conventional analysis, argue in favour of the role of triglycerides in the pathogenesis of pre‐eclampsia, regardless of the glycaemic status of the women 16,31,32 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, increasing BMI values in the pregnant population and the fear of physicians relating to GDM‐related obstetric complications seem to result in the frequent administration of low‐carbohydrate diets during pregnancy 32 . However, pregnant women are prone to hypoglycemia, and so unbalanced diets may easily lead to decreased blood glucose levels which may cause both maternal and fetal complications 33 . Thus, physicians should be particularly cautious about this issue; detailed information related to the possible adverse effects of low maternal glucose levels should be given to pregnant women during the antenatal follow‐up program.…”
Section: Discussionmentioning
confidence: 99%